(3MGTjI Ydi MGTjI JgPjH GdefWbs - (3LeGd GdOjf eMeO GdNhfSGQjs
(3ChdgG (B:s
... (3hGdeQGO ZGjJg hLeY eJYdb HeG SHb ef bhdg CJjJ hCTQJ hGdGQJMGd gh GdGJjGf HGdTYQ hZjQg ef ZjQ QhjI hCed hMGd WQa dG edjJgG hGdGTJZGd efgG HGdZjQ GdeYLe (B...s
(3BNQgG (B:s
.. (3faS GdGeQ Hae HcSQ cd aj NeS GdYhGaj ZjQ eSde Cbhd eG bjO ef GddRhe (B.. (3Hjf QHg hSGFQs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs